MISCONCEPTION RESISTANT LOAD AND INPUT DIMENSION OF STUDENT’S LEARNING STYLES ON CHEMICAL EQUILIBRIUM CONTENT - Septyadi David Eka Aryungga (PROSIDING SEMINAR KIMIA, 2015)
The purpose of this research was to determine the relationship of misconception resistant loadand input dimension of student’s learning styles on chemical equilibrium content. This research was a quantitative research using the ex post facto. The targets of this research is the students who have misconception resistant on chemical equilibrium content in SMAN 1 Kandangan, Kediri and SMAN 1 Sumenep identified conception by Certainty of Response Index (CRI) method. From 197 students, 97 students identified misconceptions resistant. Students who have misconceptions resistant administered tests of learning style on the dimension Input according to Felder and Silvermen. Misconception resistant load is categorized into three levels: low, medium, and high. The categorizing use central tendency (mean) of 6.80% and a standard deviation (standard deviation) of 4.44%. Identification ofthe student’s learning styles using instruments adopted from Felder and Silverman and analyzed with their scale. The conclusions that can be drawn from this research is on the chemical equilibrium content (1) the number of students who have misconception resistant are vary, (2) misconception resistant loadand learning styles on the input dimensionare vary, and (3) the student’s learning styles on the input dimension does not signifiacantlyaffect their misconception resistant load.